Analisis Pemasaran Minyak Nilam dari Desa Karya Baru Kecamatan Poleang Utara Kabupaten Bombana - Nurdin, Dyyah Resky; Iswandi, R. Marsuki; Yusria2, Wa Ode (Department of Agribusiness, Halu Oleo University, 2017)
This research was conducted in Karya Baru Village from May until June 2017. This research was aimed to know the marketing channel of patchouli oil from Karya Baru Village, North Poleang Sub-district of Bombana Regency, to know the efficiency of marketing channel of patchouli oil from Karya Baru Village, Poleang Utara Sub-district Bombana Regency, and to know the marketing system of patchouli oil from Karya Baru Village, Poleang Utara Sub-district Bombana Regency. Data were collected through observation, interviews using questionnaires, and documentation. Data analysis was used in this research is descriptive analysis and farmer's share analysis. The results of this research showed that there was a marketing channel of patchouli oil from Karya Baru Village, North Poleang Sub-district of Bombana Regency, namely Farmer ïƒ Small Trader ïƒ Large Trader ïƒ Consumer (Industry). Patchouli oil price at the end of a consumer was Rp450.000/kg, while marketing margin on existing marketing channel was Rp30.000/kg or 8,57 percent at small trader level and at large trader level was Rp100.000/kg or 22,22 percent. By analyzing the price factor and marketing margin, farmer's share value was 71,11 percent, which means that the marketing channel of patchouli oil located in Karya Baru Village, North Poleang Sub-district of Bombana Regency has been efficient. Patchouli oil marketing system starts from farmer level, where farmers did several times patchouli oil distillation process with yield 10-13 kg each distillation. Furthermore, farmers conduct several transactions (based on the amount of patchouli distillation process) to small traders. After the volume of patchouli oil on small traders was large enough that was 500 kg - 1,000 kg, patchouli oil distributed to a large trader in Kolaka Regency. Finally, the volume of patchouli oil in large quantities on Large Trader in Kolaka District including patchouli oil originating from Karya Baru Village of North Poleang Sub-district of Bombana Regency distributed to the Industry in Surabaya.